The Use Of Guided Question Technique To Improve Students’ Writing Skill Of Descriptive Text At Mts Al-Qur’an Harsallakum Bengkulu In The Academic Year 2024/2025 - Yola Fitri Arianata; Yuneva Yuneva; Yosi Marita (Multidisciplinary Journals, 2026)
The objective of this research was to measure improvement the students in writing skill through guided question technique of descriptive text at MTs Al-Qur’an Harsallakum Bengkulu. This reserach was conducted using classroom action. In conducting this research, the researcher used of  guided question technique to improve students writing comprehension of descriptive text. The researcher chose second grade students of MTs Al-Qur’an Harsallakum Bengkulu as the sample of the research. Class XI consists of 20 students. Therefore, the subjects of this research were 20 students. The finding of this research showed that guided question technique improved the students' writing skill at second grade of  MTs Al-Qur’an Harsallakum Bengkulu. Based on the research results In the The percentage of students who passed the The mean score improved continuallly from baseline data to cycle 1, cycle 2, and cycle 3. the end of cycle three, the result of the post test shows that there are 17 students (80%) who pass the KKM. The researcher suggested the following points: English teachers can apply  guided question technique as one of the alternative way to improve students' writing sill and to improve students' academic achievement. Further research is highly recommended to find as many as good reading strategy and technique to be applied in the classroom. By finding other strategy and technique, it hopes can create better reading comprehension for the students.